Effect of Addition of Palm Oil Shell Ash on Clay with Direct Shear Test - Christy Agata Makupiola; Rais Rachman; Irwan Lie Keng Wong (Program Studi Teknik Sipil UKI Paulus-Makassar, 2021)
The purpose of the study was to analyze the results of the physical properties of the clay used and to analyze the effect of adding oil palm shell ash to the clay on the direct shear test. From the results of testing the physical properties of the soil, the soil samples came from Jalan Yusuf Bauty, District. Somba Opu, Gowa Regency is an organic clay soil with moderate plasticity, according to the USCS soil classification system, the soil is classified as fine-grained OH group (organic clay with moderate plasticity and according to the AASTHO system the soil sample includes A-7-5. Direct Shear Test) with the addition of oil palm shell ash from the three samples, it can be seen that oil palm shell ash is able to increase cohesion (c) at each percentage addition of oil palm shell ash, but at the shear angle there is an erratic addition at each percentage addition of shell ash. palm oil, this is because oil palm shell ash only has tensile stress as a binder. From the results of research conducted, the addition of oil palm shell ash has an effect on shear strength, this shows that oil palm shell ash can be used for stabilization,